The condition of mental health of industrial enterprise’s workers according to the data of the preventive examinations - P. P. Balashov; A. V. Antukhov (Бюллетень сибирской медицины, 2009)
789 industrial enterprise’s workers, having dangerous special conditions of work, were investigated by a questionnaire, containing 24 questions and statements about psychopathological symptoms. It was determined, that the risk factors of appearance of the psychopathological symptoms are a female sex, an age more than 40 years, a loss of spouse. The investigated factors of production (character, work experience, operating schedule, education) didn’t influenced on a frequency of appearance of the psychopathological symptoms.